Study of Accidental Death Due to Road Traffic Accidental Cases Recorded at Forensic Medicine Department of Dinajpur Medical College, Dinajpur - Rahman, Kazi Golam Moakhlesur; Rahman, Md. Mizanur; Haque, Md. Rezaul (Bangladesh Journal of Medicine, 2013)
Bangladesh Journal of Medicine, Vol 23 No 2, 2012, Page 50-51 DOI: http://dx.doi.org/10.3329/bjmed.v23i2.14983